Komitmen Organisasi dan Niat Pindah Kerja - Arief Noviarakhman Zagladi (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2022)
Abstract: One of the advantages that must be maintained by a university is the quality of the lecturers it has. This study seeks to explain the effect of organizational commitment on the intention to change jobs in private college lecturers in Malang City, East Java. The choice of Malang city was done because Malang City is well-known in Indonesia as a student city that has many universities. This study uses a population of 794 lecturers spread over 20 private colleges in Malang City. Samples were taken as many as 89 people in a balanced manner and analyzed by regression analysis. The results from this study showed that there was no significant effect between organizational commitment and the intention to change lecturers' jobs. Keywords: organizational commitment, intention to change jobs, private college